Collaboration between Public Research Institutes and Universities: A Study of Industrial Technology Research Institute, Taiwan - Wong, C.Y.; Hu, M.C.; Shiu, J.W. (SAGE Publications (UK and US), 2015)
This study examines the linkages between Taiwan’s Industrial Technology Research Institute (ITRI) and universities. It employs the government–university (G–U) relation of triple helix framework to assess collaboration patterns between ITRI and the top universities of Taiwan over two phases of economic development, that is, the catching-up phase in the 1990s and the subsequent post catching-up phase over the 2000s. We highlight the collaborative dynamics in terms of ITRI’s (a) (co-) evolving knowledge capital, (b) strategic collaboration mode, (c) co-publication in scientific papers, (d) co-owned patents, (e) forward and backward citations and (f) science-based patents. Our systematic review of the role of ITRI in both catching-up and post catching-up phases will provide a useful guide for policy makers in other economies (such as Malaysia and Hong Kong) that aspire to define a similar role for their public research institutions.